South Africa's foreign policy aspirations and the National Development Plan (NDP 2030): the role of soft power. Issue 3 (3rd July 2017) - Isike, Christopher; Ogunnubi, Olusola
ABSTRACT: Chapter 7 of the NDP 2030 articulates a foreign policy vision for South Africa over two decades. While the NDP acknowledges the place of 'soft power' in realising this vision, it remains doubtful whether South Africa will indeed take advantage of the enormous gains offered by soft power as a foreign policy lever. This paper examines the role of soft power in achieving the foreign policy mandates prescribed in the Plan. It argues that, like other regional powers such as China, South Africa needs to pay more attention to its soft power attributes if it is to fast-track the successful implementation of its foreign policy ambitions for 2030. We conclude that sustaining South Africa's rising position and influence in the international system and in Africa, will largely depend on its ability to consciously adjust its foreign policy trajectories – in the long term – in tandem with its soft power resources and competences.